Advanced technologies and methodologies for risk management in the global transport of dangerous goods - Bersani, Chiara (NATO science for peace and security series. Human and societal dynamics ;, 2008)
Logistics has become a strategic factor for development and competition. Terrorist attacks, such as 11th of September 2001 in the USA, have caused the introduction of rules and procedures, which affect the overall logistics showing the vulnerability of the global economy. This book presents the status of research on dangerous goods transport.